Pengaruh Ekstrak Daun Nangka (Artocarpus heterophyllus lam) terhadap Kualitas Telur Itik yang Diawetkan - Ananda, Suci; Rusmah, Lutfiyah Mutmainna; Rusny, Rusny (Universitas Islam Negeri Alauddin Makassar, 2025)
Eggs are one of the main products produced by poultry with high nutritional value. Eggs have the disadvantage of being easily damaged, either in the form of physical damage, chemical damage and damage caused by microbes. This study aims to determine the effect of the quality of duck eggs preserved with jackfruit leaf extract (Artocarpus heteropyhllus lam.) and what changes occur after soaking. This research method uses a Completely Randomized Design (CRD) Factorial with 5 treatments and 4 replications. The research design is based on the jackfruit leaf extract used, the first treatment is (PO) = 0% (control, without jackfruit leaf extract), and (P1) = 15% (using jackfruit leaf extract) with a soaking time of 22 hours, (P2) = 30% (using jackfruit leaf extract) with a soaking time of 26 hours, and (P3) = 45% (using jackfruit leaf extract) with a soaking time of 30 hours and (P4) = 60% (using jackfruit leaf extract) with a soaking time of 34 hours. The parameters observed were the shrinkage of egg weight, air cavity, color and pH of duck eggs. The results showed that the addition of jackfruit leaf extract had no significant effect (P>0.05) on the shrinkage of egg weight, air cavity, color and pH because it did not cause significant changes in duck eggs.